2016
DOI: 10.1177/0095327x16667087
|View full text |Cite
|
Sign up to set email alerts
|

The Military Role in Filling the Security Gap After Armed Conflict

Abstract: During stabilization operations, the host nation and the international community are often confronted with a security gap, which could be a prelude to an explosive growth of crime and public disorder. In the absence of a functioning local police, an alternative is that the (international) military temporarily intervenes as interim police. This article analyzes how the Netherlands’ military performed during security gaps in three (post)conflict areas: Bosnia and Herzegovina, Kosovo, and Iraq. It concludes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They used the data to make preliminary observations about the partnerships at the case study location and to theorize about the nature of the "uneasy" partnerships they observed. Neuteboom and Soeters (2017) explored how the Netherlands military personnel performed during periods when the military assumed the police function in three post-conflict areas. This retrospective comparative case study used intensive in-depth interviews and document analysis to trace the process used by the military organizations to deal with the security gap.…”
Section: How "Military and Society" Is Studiedmentioning
confidence: 99%
“…They used the data to make preliminary observations about the partnerships at the case study location and to theorize about the nature of the "uneasy" partnerships they observed. Neuteboom and Soeters (2017) explored how the Netherlands military personnel performed during periods when the military assumed the police function in three post-conflict areas. This retrospective comparative case study used intensive in-depth interviews and document analysis to trace the process used by the military organizations to deal with the security gap.…”
Section: How "Military and Society" Is Studiedmentioning
confidence: 99%
“…This may require soldiers to depart from their “comfort zones” and concede to ambiguity: “to balance ambiguities, while exploring areas of compromise and agreement... [and] to live with insoluable problems” (Janowitz, 1971, pp. 275-276; Neuteboom & Soeters, 2017, p. 726).…”
Section: The Pragmatistmentioning
confidence: 99%
“…It might also support critical thinking to help soldiers adapt, seek to build relationships, and work cooperatively with other agencies. Lastly, Joseph Soeters of the Netherlands Defense Academy applies a pragmatist mindset when exploring “peaceweaving”, positive peace, dualisms in conflict environments, and closing security gaps in post-conflict stabilization operations (Neuteboom & Soeters, 2017; Shields & Soeters, 2017).…”
Section: The Pragmatistmentioning
confidence: 99%
See 1 more Smart Citation